Indoxyl sulfate, a uremic toxin in chronic kidney disease, suppresses both bone formation and bone resorption. Issue 8 (20th July 2017) - Watanabe, Kenta; Tominari, Tsukasa; Hirata, Michiko; Matsumoto, Chiho; Hirata, Junya; Murphy, Gillian; Nagase, Hideaki; Miyaura, Chisato; Inada, Masaki
Abstract : Abnormalities of bone turnover are commonly observed in patients with chronic kidney disease (CKD), and the low‐turnover bone disease is considered to be associated with low serum parathyroid hormone (PTH) levels and skeletal resistance to PTH. Indoxyl sulfate (IS) is a representative uremic toxin that accumulates in the blood of patients with CKD. Recently, we have reported that IS exacerbates low bone turnover induced by parathyroidectomy (PTX) in adult rats, and suggested that IS directly induces low bone turnover through the inhibition of bone formation by mechanisms unrelated to skeletal resistance to PTH. To define the direct action of IS in bone turnover, we examined the effects of IS on bone formation and bone resorption in vitro . In cultures of mouse primary osteoblasts, IS suppressed the expression of osterix, osteocalcin, and bone morphogenetic protein 2 (BMP2) mRNA and clearly inhibited the formation of mineralized bone nodules. Therefore, IS directly acts on osteoblastic cells to suppress bone formation. On the other hand, IS suppressed interleukin (IL)‐1‐induced osteoclast formation in cocultures of bone marrow cells and osteoblasts, and IL‐1‐induced bone resorption in calvarial organ cultures. In cultures of osteoblasts, IS suppressed the mRNA expression of RANKL, the receptor activator of NF‐κB ligand, which is a pivotal factor for osteoclast differentiation. Moreover, IS acted on osteoclast precursor, bone marrow‐derived macrophages and RAW264.7 cells, and suppressed RANKL‐dependent differentiation into mature osteoclasts. IS may induce low‐turnover bone disease in patients with CKD by its direct action on both osteoblasts and osteoclast precursors to suppress bone formation and bone resorption. Abstract : Indoxyl sulfate (IS) is a representative uremic toxin that accumulates in the blood of chronic kidney disease (CKD) patients. IS suppressed the formation of both osteoclasts (responsible for bone resorption) and osteoblastic bone nodules. We suggest here that the exacerbation of low bone turnover in CKD patients may be due to the direct action of IS in bone tissues.